The Impact of Family Intactness on Family Functioning, Parental Control, and Parent–Child Relational Qualities in a Chinese Context - Shek, Daniel T. L.; Xie, Qiuzhi; Lin, Li (Frontiers in Pediatrics, 2015)
The current study investigated the differences between intact and non-intact families in family processes, including systematic family functioning, parental behavioral control, parental psychological control, and parent–child relational qualities. The participants were 3,328 Secondary One students, with a mean age of 12.59 years, recruited from 28 secondary schools in Hong Kong. Four validated scales were used to assess family processes. Results showed that adolescents in non-intact families perceived relatively poorer family functioning, lower level of paternal and maternal behavioral control, lower level of paternal psychological control, and poorer parent–child relational qualities than did adolescents in intact families. This generally indicated that family processes were poorer in non-intact families, compared with those in intact families. The theoretical and practical implications of the findings were discussed.